1438 The Past, Present and Future Management of Complex Chyle Fistulae. (12th October 2021) - Temperley, H; Waters, C; Carey, J; Donlon, N E; Donohoe, C L; Ravi, N; Reynolds, J V
Abstract: Background: Chyle leak/fistula is a rare complication of oesophageal surgery, usually consequent on an unintended breach of the thoracic duct, its tributaries, or the cisterna chyli. For high volume persistent leaks further surgery has been the traditional approach, however two cases have resulted in a new management approach at this Centre. Case Series: The first patient, a 49-year-old, developed high volume drain output post three stage oesophagectomy. His jejunostomy feeding was discontinued, total parenteral nutrition and a somatostatin analogue, were commenced. Despite these measures, the drain output remained >1.5litres per day and an exploratory thoracotomy was performed. The second patient, an 81-year-old underwent a transhiatal-oesophagectomy. On postoperative day 10 he developed acute onset shortness of breath, CXR demonstrated a large left sided pleural effusion. CT thorax demonstrated multiloculated complex pleural effusions. US guided pig tail drain was placed in the largest targetable effusion. The fluid was chylous in appearance. In both cases, an interventional radiological approach, not previously performed at this centre, provided definitive management. Lymphangiography was performed via injection of 1mL of Lipoidol® every 5 minutes into the inguinal lymph nodes to identify the cisterna chyli. A guidewire was advanced via the cisterna chyli with coils and glue used to embolize the leaking tracts. Discussion: The lessons from this experience provide an algorithm for the management of chyle leaks, that will change practice at this centre. Embolization or disruption of thoracic duct and cisterna chyli leaks will be first line therapy for complex chyle leaks, with surgery reserved for where this fails.